Design and experimentation of sampled-data controller in T-S fuzzy systems with input saturation through the use of linear switching methods - YeongJae Kim; YongGwon Lee; SeungHoon Lee; Palanisamy Selvaraj; Ramalingam Sakthivel; OhMin Kwon (AIMS Mathematics, 2024)
In this study, the stability and stabilization analyses are discussed for Takagi-Sugeno (T-S) fuzzy systems with input saturation. A fuzzy-based sampled-data control is designed to stabilize the T-S fuzzy systems. Based on the Lyapunov method and some integral inequality techniques, a set of sufficient conditions is obtained as linear matrix inequality (LMI) constraints to guarantee the asymptotic stability of the considered system. In this process, the linear switching method is utilized to design a controller that is dependent on the membership function, and an integral inequality is utilized. Additionally, determination of the controller parameters is achieved by resolving a series of LMI constraints. The effectiveness of these criteria is demonstrated through a real system that is modeled by the T-S system.